Legal Review of Financial Technology Peer To Peer Lending Based on Indonesian Collateral Law Perspective - Ningsih, Ayup Suran (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2020)
In fulfilling everyday needs, certainly needing equipment and supporting equipment in practice. However, due to limited capital, the background of the birth of legal entities from the government to the private sector offered a program to lend money which was then used for capital. In the process, this loan is often called a credit agreement in which the minimum requirement is a guarantee that will later be used as a collateral object. The guarantee acts as an addition (accesoir) to the main agreement which is to convince the creditor of the assets of the debtor and their ability to make payments later. Because not everyone has sufficient assets to make a loan, a guarantee institution arises that provides a loan program without using collateral. In connection with the development of technology, a new program was born, namely peer to peer lending based on financial technology. Ease in requirements and track record written in a system is the attraction of this type of loan, but because it is regulated by the system, there can be a mismatch of what is promised.